TRADISI RUWAHAN SEBAGAI ALAT KOMUNIKASI ANTAR UMAT BERAGAMA DI DESA CANDIHARJO MOJOKERTO - Melanda warsetiyo putri; agus machfud fauzi (Jurnal Ilmiah Sosiologi Agama (JISA), 2021)
Communication that is often encountered by the people of Candiharjo Village is cross-cultural communication between Muslims and non-Muslims. The communication that occurs can be seen through the implementation of the ruwahan tradition. The ruwahan tradition is one of the Javanese traditions that is held before the holy month of Ramadan. The ruwahan tradition is interpreted as a symbol of gratitude to the creator of the farmers so that their crops are abundant and as a source of safety and blessings. The research objective was to analyze the ruwahan tradition as a means of communication between religious communities in the village of Candiharjo Mojokerto. This study uses qualitative methods by means of direct interviews and applying 3M health protocols. The theory used is Emile Durkheim's theory of mechanical solidarity. The result of the research states that the ruwahan tradition is one of the activities that creates harmony between religious communities. In the ruwahan tradition, there are several activities, such as salvation (kenduren), mutual cooperation to clean the village, and the pilgrimage to the family grave. These activities create communication and build tolerance among religious communities. This attitude of tolerance is mutual respect, respect, and so on.